An Evaluation of Qualities of Nuclear Medicine Technology Programs and Graduates Leading to Employability - Nielsen, Cybil J.; Brosmer, Sarah S.; Byrne, Patrick J.; Jennings, S. Gregory (Journal of nuclear medicine technology, 2019)
Our rationale was to evaluate how the qualities of nuclear medicine technology (NMT) programs and graduates associate with employability. We identified all Nuclear Medicine Technology Certification Board applicants who passed the entry-level NMT examination between 2012 and 2017. Certificants were e-mailed a survey with questions on graduate qualities, program qualities, and initial employment. Each quality was quantified. Age, sex, and desired employment within or outside the United States were also documented. An employability scale was created from the initial employment questions. Subjects were separated into 4 employability groups based on their employability score: poorly employable, marginally employable, satisfactorily employable, and optimally employable. An ANOVA test was performed on each quality using the 4 employability groups; a value of less than 0.05 was considered significant. Of the 3,930 surveys distributed, 885 (22.5%) were completed and returned. Six of the 10 qualities evaluated were significantly associated with employability: overall education ( < 0.01), number of clinic hours ( < 0.01), grade-point average ( < 0.01), number of schools within a 100-mile (161-km) radius ( < 0.01), number of attempts to pass the board examination ( < 0.01), and number of clinics ( = 0.04). The qualities that were not statistically significant were age, sex, employment location sought, board score, single versus dual certification, program level of education, and number of graduates in the class. There are multiple graduate and program qualities that are predictive of the employability of NMT graduates.